Thermal and combustion behavior of furan resin/silica nanocomposites. (June 2015) - Monti, Marco; Hoydonckx, Hans; Stappers, Frank; Camino, Giovanni
Graphical abstract: Highlights: Furan resin is a bio-based thermosetting polymer with excellent thermal and combustion behavior. Silica nanoparticles can further improve the thermal and combustion behavior of the furan resin. A detailed description of the thermal degradation mechanism of the furan resin is proposed. Abstract: In this paper, we report the development of furan resin nanocomposites, filled with silica nanoparticles. In order to have a dispersion procedure, which could be easily up-scalable to the industrial level, a commercially available water-based suspension of silica particles was used. This was possible thanks to the fact that water is a good solvent of furan resin. Different treatments with silanes were performed in order to improve the interaction between the silica particles and the furan matrix. As a result, the thermal oxidative resistance of the furan resin is improved with also a minor improvement of fire reaction, which is already quite substantial in the pristine resin.